Design of passive coolers for light-emitting diode lamps using topology optimisation. (July 2018) - Alexandersen, Joe; Sigmund, Ole; Meyer, Knud Erik; Lazarov, Boyan Stefanov
Graphical abstract: Highlights: Topology optimisation is applied to the design of passive cooling of LED lamps. Resulting designs are 26% more efficient than a reference regular lattice design. Designs are 10–20% better than optimised commercially available pin-fin designs Optimised structures with additional symmetry are less sensitive to orientation. Optimised topologies yield new insight in design of passive cooling devices. Abstract: Topology optimised designs for passive cooling of light-emitting diode (LED) lamps are investigated through extensive numerical parameter studies. The designs are optimised for either horizontal or vertical orientations and are compared to a lattice-fin design as well as a simple parameter optimised commercial pin fin design. The different orientations result in significant differences in topologies. The optimisation favours placing material at outer boundaries of the design domain, leaving a hollow core that allows the buoyancy forces to accelerate the air to higher speeds. Investigations show that increasing design symmetry yields performance with less sensitivity to orientation with a minor loss in mean performance. The topology-optimised designs of heat sinks for natural convection yield a 26% lower package temperature using around 12% less material compared to the lattice-fin design, while maintaining low sensitivity to orientation. Furthermore, they exhibit several defining features and provide insight and general guidelines for the design of passive coolers for LED lamps.